The Use of Android-Based PhET Simulation as an Effort to Improve Students’ Critical Thinking Skills during the Covid-19 Pandemic - Hasyim, Faiz; Prastowo, Tjipto; Jatmiko, Budi (International Journal of Interactive Mobile Technologies (iJIM), 2020)
Covid-19 spurs teachers to carry out online learning. This study aimed to analyze the improvement of students’ critical thinking skills through online learning based on Android-based PhET Simulation. This research was Quasi-Experimental using one group pre-test and post-test design involving 27 students of class VIII who program science subjects at MTs Alif Laam Miim Surabaya, Indonesia. The research instrument used critical thinking skills tests that have met valid and reliable requirements. Before and after learning activities, students were given a pre-test and a post-test. The data collected was analyzed descriptively quantitatively. The results showed that there was an increase in students’ critical thinking skills with an average N-gain of 0.57, in the medium category. The highest N-gain was achieved in the "interpretation" indicator, which is 0.83 in the high category and the lowest in the "analysis" indicator, which is 0.39 in the moderate category. This study concluded that learning science by using an Android-based PhET Simulation can improve the critical thinking skills of junior high school students.